Design of Melodi Nusantara Rhythm Game to Introduce Traditional Indonesians Song - Sugiarto, Lie Luky Andreas; Nugroho, Agus Cahyo; Prasetya, FX Hendra (Journal of Business and Technology, 2023)
At The culture of traditional music and songs in Indonesia is one of the results of intellectual and cultural richness, which plays an important role in the lives of traditional communities. In addition, traditional music and songs are also national assets that embody strategic values for both Indonesia and foreign parties. Therefore, there is a need to protect traditional music and songs in Indonesia. "Melodi Nusantara" is the name of a game developed to support and introduce traditional music and songs of Indonesia. The game "Melodi Nusantara" is a rhythm game genre. The rhythm game genre is very popular and loved by all, and this game requires players to follow the rhythm of a song. This game is very suitable for listening to music while playing. With the existence of the "Melodi Nusantara" game, it is hoped that players will be able to recognize the music culture of each region in Indonesia. And researchers can also see if the "Melodi Nusantara" game will continue to be useful for players and if they would want play the "Melodi Nusantara" game in the future.